A contribuição da hierarquia de concerns para o processo de projeto de sistema produto-serviço - Jorge, Gabriel Gallina (Universidade do Vale do Rio dos Sinos, 2017)
A Product-Service System project covers the creation of artifacts and their mutual relationships, taking into account both tangible and intangible dimensions in the composition of the offer and how this can be delivered to user in the most complete way possible. In order to meet the users' needs, first it is needed to understand what their concerns are in relation to what is about to be designed. Through the Appraisals' Theory it is possible to gain this insight and also provide the designer with the tools needed to apply it to the project. The objective of this research is to evaluate the use of a hierarchically organized concern profile in the development of a PSS project and to identify its contribution to this process. The PSS context under study are street food events based in Porto Alegre, Brazil. In order to conduct this research, we have first used qualitative methods (13 in-depth interviews) to identify concerns and elaborate a concern profile for patrons and non-patrons. We have then applied a quantitative method (survey with 328 users) to establish descriptive parameters for the concern statements as variables. A statistical procedure of multivariate data analysis has been performed on these results, obtaining a hierarchy of the concern statements. The last research step has been a project stage, organized in two workshops with professionals discussing and developing a street food event project, with only one group having access to the hierarchized concern profile. Our results show that the hierarchization of concerns can contribute by providing the designer with more qualified resources about the user, reducing risks during the design process, and promoting a PSS more focused on the user's concerns. These findings have practical and theoretical implications for research and processes involving user perspective in PSS design.
Keywords: Design; Sistema produto-serviço; Teoria dos Appraisals; Perfil de concerns; Processo de projeto; Design; Product-service system; Appraisals’ Theory; Concern profile; Design process; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial